Learning Process of Reading Multimodal Narrative Text: Promoting Students' Social and Emotional Competencies - Nurviyani, Vina (Linguistics and ELT Journal, 2023)
This study explored the learning process of reading multimodal Narrative text promoting students' social and emotional competencies. Moreover, the advantages and disadvantages of the learning process were investigated. A qualitative (a single case study) through observations, open-ended questionnaires, and documents was applied as the research design. Forty-one college students studying at a private university participated as the research participants. The research results show that the learning processes of multimodal Narrative text promoting students' social and emotional competencies are manifested in three stages (RSR): 1) Reading text, 2) Synthesizing text, and 3) Retelling text. In the stages of RSR, the students read the multimodal Narrative text presented on the webs, then synthesize it using digital apps and inserted by an image; in the end, they  retold the text orally in front of the class for three to five minutes. Some learning activities of reading multimodal Narrative text promoting students’ social and emotional competencies conducted in the stages, i.e., a) they  had to manage their minds and made the responsible decision for selecting the multimodal Narrative text and the digital apps used to summarize or synthesize the text, b) they had to control their emotions and confidence when retelling the text orally in front of their friends, and c) they should show empathy and good responses as their friends perform and retell the text. The students with good social and emotional competencies successfully participate in all stages. However, some students needed confidence improvement in synthesizing and retelling the text. They needed more practice and guidance to develop their social and emotional competencies, particularly self-awareness and self-management competence. In addition, all stages of the learning process were carried out over a long time and a long process. Nevertheless, the learning process of reading multimodal Narrative text had encouraged the student's social and emotional, and literacy competencies.